Ripeness Classification Of Oil Palm Fruit To Ensure Optimum Quantity Of Oil Using Image Processing Techniques - Munirah binti Abdul Hamid, Munirah (2010)

(untitled)
The project involves on detecting optimum quantity and quality of oil based on the ripeness of oil palm fruit using suitable Digital Image Processing Techniques. The objective of this project is to develop an easy and flexible system where user can use the system to classify the maturity of fruit using CCD camera and Matlab-Image Processing Toolbox.